(3eNJUQ OdGFd GdEYLGRs - (3ceGd GdOjf CHh eMeO YHO GdhGMO Hf YHO GdcQje Hf Nda Hf fHgGf GdCfUGQj Ke GdSeGcis; (3CHh HcQ YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, YHO GdbGgQ GdLQLGfj,J (B471 (3g` s ((3HYdHc GdeMQhSI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfWb CdSfI GdCbdGe HEMcGe GdCMcGe CLeYgG cJGH OdGFd GdEYLGR ddEeGe YHO GdbGOQ GdLQLGfi QMeg Gddg hbO QJHJg Ydi ShGHb hebGUO hdhGMb CeG GdShGHb aai GdebOeGJ s
(3BNQgG (B:s
(3hbO CWdYJc ai gPG GdcJGH Ydi QjGV cfJ YfgG ai YejGA MTQfG Gddg JYGdi ai ReQJge hCeGJfG Ydi eMHJge Cfg Ydi Pdc bOjQ hHGdELGHI LOjQ hgh MSHfG hfYe Gdhcjd s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B606s
Keywords: (3GdHdGZIs